Novel Trends in the Traveling Salesman Problem - Davendra, Donald; Bialic-Davendra, Magdalena; Davendra, Donald; Bialic-Davendra, Magdalena (IntechOpen, 2020)
The Traveling Salesman Problem (TSP) is widely considered one of the most intensively studied problems in computational mathematics and operations research. Since its inception, it has become the poster child for computational complexity research. A number of problems have been transformed to a TSP problem and its application base now extends into scheduling, manufacturing, routing, and logistics. With the advent of high-performance computing and advanced meta-heuristics such as GPU programming and swarm-based algorithms, the TSP problem is positioned firmly as the go-to problem for the development of the next generation of high-performance intelligent heuristics. This book looks to leverage some of these new paradigms for both students and researchers in this field.
English
Keywords: Discrete mathematics; Discrete mathematics